Degradable antibacterial film material and preparation method thereof
By loading natural antibacterial agents into the modified flame retardant composite filler in the film material and adding modified additives, the problem of flammable and flame retardant properties of the film material is solved, and strong antibacterial, antioxidant and flame retardant properties are achieved, while improving mechanical properties.
Patent Information
- Application Number
- CN202510295987.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-08
AI Technical Summary
The existing film materials are flammable as a whole, and the inorganic mineral fillers are unevenly dispersed in the film, resulting in flame retardant performance not meeting the requirements and causing a decrease in mechanical properties.
By loading natural antibacterial agents into the modified flame retardant composite filler by vacuum impregnation, a slow release rate is achieved, and the mechanical properties, antibacterial properties and flame retardant properties of the film material are enhanced by the addition of modified additives.
The long-term antibacterial and antioxidant activities of the film material are achieved, while enhancing its flame retardant properties and mechanical properties, and regulating the diffusion/permeation of gas and water molecules.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of film materials, and in particular relates to a degradable antibacterial film material and a preparation method thereof. Background Art
[0002] Food safety issues are related to the health of consumers and the sustainable development of food-related industries. As consumers pay more and more attention to food safety and preservation, preventing food quality degradation caused by oxidation, rancidity and pathogenic microbial infection has become a hot topic of concern in the food industry and academia. Among them, the use of antibacterial and antioxidant active packaging is an advanced and effective means to prevent the loss of food nutrients and microbial infection from causing food quality degradation or safety risks. However, traditional packaging materials do not have the function of actively regulating the internal environment of the packaging. In order to provide better protection for foods that are sensitive to oxygen, microorganisms, etc., active packaging has been developed and applied to improve food quality and safety.
[0003] Biodegradable polyester is a type of high molecular weight polyester that can be degraded by microorganisms. In view of the potential dangers of synthetic antioxidants, people have also been committed to finding safe and effective antioxidants from various natural products for food protection in recent years. Plant essential oils and plant extracts are the most common sources of natural antioxidants, but they have defects such as unstable physical and chemical properties or short duration of effectiveness, and are easily affected by factors such as light, temperature and oxygen, which affects their application in the field of food packaging.
[0004] In addition, the existing film materials are flammable as a whole. The Chinese patent with application number CN 201410777429.1 discloses a degradable flame-retardant plastic film and a preparation method thereof. The raw material components and weight proportions are: 85 parts of polyethylene, 20-30 parts of polylactic acid, 65-80 parts of PBM degradation material, 10-15 parts of filler, 5-10 parts of pullulan, 2-4 parts of antioxidant, 1-1.5 parts of ultraviolet absorber, and 25-30 parts of nano flame retardant composite. The patent adds inorganic mineral materials to the film raw materials to make the plastic film have certain flame retardant properties. However, the inorganic mineral fillers have the defects of easy agglomeration and poor compatibility with the polymer matrix, and are difficult to be evenly dispersed in the plastic film, so that the flame retardant properties of the plastic film still fail to meet the use requirements, and to a certain extent, the mechanical properties of the film will be reduced. Summary of the invention
[0005] In order to solve the deficiencies mentioned in the above-mentioned background technology, the purpose of the present invention is to provide a degradable antibacterial film material and a preparation method thereof, load the natural antibacterial agent into the modified flame-retardant composite filler by vacuum impregnation to achieve a slow release rate, and effectively enhance the mechanical properties, antibacterial properties and flame retardant properties of the film material by adding modified additives, while regulating the diffusion / permeation of gas and water molecules in the film.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A degradable antibacterial film material comprises the following components in parts by weight: 75-100 parts of a degradable base resin, 5-15 parts of a modified additive, 1-3 parts of a plasticizer, and 1-3 parts of a lubricant; The modified additive is prepared by loading a natural antibacterial agent on a modified flame-retardant composite filler; wherein the modified flame-retardant composite filler is prepared by reacting cinnamaldehyde with the flame-retardant composite filler to form a complex with zinc acetate dihydrate by Schiff base reaction; The flame-retardant composite filler is prepared by a ring-opening reaction between an epoxidized composite filler and 1,5-naphthalenediamine, followed by a nucleophilic substitution reaction with phytic acid; the epoxidized composite filler is prepared by a sol-gel method for preparing a composite filler of montmorillonite loaded with nano-titanium dioxide, and then modified with 3-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0007] Preferably, the degradable matrix resin is one or more combinations of polybutylene terephthalate-adipate, polylactic acid, poly-ε-caprolactone, polyglycolic acid, and polyhydroxyalkanoate.
[0008] Preferably, the plasticizer is one or more combinations of tributyl citrate, diisononyl phthalate, dibutyl phthalate, and acetyl tributyl citrate; and the lubricant is one or more combinations of stearic acid, zinc stearate, polyethylene wax, and paraffin.
[0009] Preferably, the preparation method of the modified additive comprises the following steps: (1) Tetrabutyl titanate and anhydrous ethanol are stirred and mixed, montmorillonite and deionized water are added, and the stirring is continued for 0.5 to 1 hour, and then a mixed solution of acetic acid and deionized water is added, and the mixture is stirred evenly and allowed to stand for 20 to 24 hours, and then dried in an oven, and then calcined at 550 to 650° C. for 4 to 7 hours to prepare a composite filler; (2) ultrasonically dispersing the composite filler in toluene, then adding a mixed solution of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and toluene, stirring and reacting at 80-95°C for 5-6 hours, and after the reaction is completed, filtering, washing and drying to prepare an epoxidized composite filler; (3) ultrasonically dispersing the epoxidized composite filler in anhydrous ethanol, then adding a mixed solution of 1,5-naphthalenediamine and anhydrous ethanol, stirring and reacting at 55-70° C. for 5-8 hours, and filtering, washing and drying after the reaction to obtain an amino composite filler; (4) ultrasonically dispersing the amino composite filler in anhydrous ethanol to obtain a dispersion, then dissolving the phytic acid aqueous solution in anhydrous ethanol and adding it to the dispersion, stirring and reacting at 60-75° C. for 4-6 hours, filtering, washing and drying after the reaction is completed to prepare a flame-retardant composite filler; (5) Ultrasonic dispersion of flame-retardant composite filler in anhydrous ethanol, adding cinnamaldehyde and stirring the mixture, stirring the mixture at 60-70°C for 28-36 hours under nitrogen conditions, then adding a mixed solution of zinc acetate dihydrate and deionized water, stirring the mixture at 40-50°C for 4-6 hours, and after the reaction is completed, centrifuging, washing, and drying to obtain a modified flame-retardant composite filler; (6) The natural antibacterial agent is added to the modified flame retardant composite filler by vacuum adsorption method, mixed evenly, and then vacuum adsorbed for 1 to 3 hours. After centrifugation to separate the excess natural antibacterial agent, the modified additive is prepared.
[0010] Preferably, in step (2), the mass ratio of the composite filler to 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 1:0.4-0.7.
[0011] Preferably, in step (3), the mass ratio of the epoxidized composite filler to 1,5-naphthalenediamine is 1:0.25-0.45.
[0012] Preferably, the mass concentration of the phytic acid aqueous solution in step (4) is 40-60wt%; and the mass ratio of the amino composite filler to the phytic acid aqueous solution is 1:1-2.5.
[0013] Preferably, in step (5), the addition ratio of the flame retardant composite filler, cinnamaldehyde and zinc acetate dihydrate is 1 g: 40-70 mL: 3.5-5.5 g.
[0014] Preferably, the natural antibacterial agent in step (6) is one or more combinations of clove essential oil, cinnamon essential oil, lemongrass essential oil, thyme essential oil, garlic essential oil, oregano essential oil, lemon essential oil, tea tree essential oil, rosemary extract, olive leaf extract, and grape seed extract.
[0015] The method for preparing the above-mentioned degradable antibacterial film material comprises the following steps: S1, taking parts by weight of a biodegradable base resin, a modifying additive, a plasticizer and a lubricant into a mixer, placing the mixture at 150-200° C. and stirring for 0.5-1 h, and then extruding and granulating the mixture at 200-230° C. using a twin-screw extruder to obtain a mixture; S2. Blowing the mixture into the degradable antibacterial film material through a film blowing machine, wherein the film blowing machine is a three-screw film blowing machine, the screw processing temperature is set to 160-180° C., and the blowing die processing temperature is set to 190-210° C.
[0016] Beneficial effects of the present invention: The present invention uses a sol-gel method to prepare a composite filler of montmorillonite-stabilized anatase-phase nano-titanium dioxide, and then uses the silicon hydroxyl group in the structure of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to undergo a condensation reaction with the hydroxyl group on the surface of the composite filler to prepare an epoxidized composite filler, and then uses the epoxidized composite filler to undergo a ring-opening reaction with an amino group at one end of the structure of 1,5-naphthalenediamine to form an -OH group and an -NH group to prepare an amino composite filler, and further uses phytic acid to undergo a nucleophilic substitution reaction with the -OH group and the -NH group in the structure of the amino composite filler to prepare a flame retardant composite containing nitrogen, phosphorus and silicon elements. The composite filler is then reacted with the amino groups in the flame retardant composite filler structure and the cinnamaldehyde to undergo Schiff base reaction, and zinc acetate dihydrate is used to form a zinc particle complex with multiple phosphate hydroxyl groups introduced into the flame retardant composite filler structure to prepare a modified flame retardant composite filler, wherein cinnamaldehyde is used as a natural antibacterial material, and it is grafted with the flame retardant composite filler to introduce hydrophobic benzene ring groups and antibacterial Schiff base groups, showing more prominent antibacterial activity, and zinc ions are used as good catalytic carbonizing agents and smoke suppressants. The zinc ions are introduced into the flame retardant composite filler containing nitrogen, phosphorus and silicon elements, which can further improve the flame retardant and smoke suppression efficiency of the flame retardant system, thereby improving the flame retardant properties of the material. The invention utilizes plant essential oil or plant extract as a natural antibacterial agent, nano titanium dioxide as an inorganic antibacterial agent, and montmorillonite as a porous material, and loads the natural antibacterial agent into a modified flame-retardant composite filler by a vacuum impregnation method to achieve a slow release rate, thereby obtaining a strong antioxidant and long-acting antibacterial activity, and can have the advantages of both inorganic antibacterial materials and organic antibacterial materials, and exert complementary and synergistic antibacterial effects. The addition of modified additives can effectively enhance the mechanical properties of the film material, and at the same time regulate the diffusion / permeation of gas and water molecules in the film. In addition, the introduced nitrogen, phosphorus, silicon elements and zinc ions give the film material excellent flame retardant properties. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1 A method for preparing a modified additive comprises the following steps: (1) 7 mL of tetrabutyl titanate and 7 mL of anhydrous ethanol were stirred and mixed, 5 g of montmorillonite and 40 mL of deionized water were added, and the mixture was stirred for 0.5 h. Then, a mixed solution of 5 mL of acetic acid and 5 mL of deionized water was added, and the mixture was stirred evenly and allowed to stand for 24 h. The mixture was then dried in an oven and calcined at 600 °C for 5 h to prepare a composite filler. (2) 2.5 g of the composite filler was ultrasonically dispersed in 40 mL of toluene, and then a mixed solution of 1.2 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 20 mL of toluene was added, and the mixture was stirred at 85 °C for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried to prepare an epoxidized composite filler; (3) 2.5 g of the epoxidized composite filler was ultrasonically dispersed in 50 mL of anhydrous ethanol, and then a mixed solution of 0.73 g of 1,5-naphthalenediamine and 20 mL of anhydrous ethanol was added, and the mixture was stirred at 65 °C for 7 h. After the reaction was completed, the mixture was filtered, washed, and dried to prepare an amino composite filler; (4) 2.5 g of the amino composite filler was ultrasonically dispersed in 100 mL of anhydrous ethanol to obtain a dispersion, and then 2.5 g of a 50 wt% phytic acid aqueous solution was dissolved in 50 mL of anhydrous ethanol and added to the dispersion. The mixture was stirred at 70° C. for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a flame-retardant composite filler. (5) 1 g of flame-retardant composite filler was ultrasonically dispersed in 120 mL of anhydrous ethanol, 60 mL of cinnamaldehyde was added and stirred, and the mixture was stirred and reacted at 65 °C for 32 h under nitrogen conditions. Then, a mixed solution of 4.3 g of zinc acetate dihydrate and 50 mL of deionized water was added and stirred and reacted at 45 °C for 6 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to prepare a modified flame-retardant composite filler; (6) Cinnamon essential oil was added to the modified flame retardant composite filler by vacuum adsorption method. The mass ratio of cinnamon essential oil to modified flame retardant composite filler was 1:5. The mixture was evenly mixed and then placed under 0.1 MPa for vacuum adsorption for 2 h. After centrifugation to separate excess natural antibacterial agent, the modified additive was prepared.
[0019] Example 2 A degradable antibacterial film material comprises the following components in parts by weight: 77 parts of polybutylene terephthalate-adipate, 5 parts of the modifying additive prepared in Example 1, 1.2 parts of tributyl citrate as a plasticizer, and 1 part of stearic acid as a lubricant.
[0020] The method for preparing the above-mentioned degradable antibacterial film material comprises the following steps: S1, taking parts by weight of polybutylene terephthalate-adipate, a modifying additive, a plasticizer and a lubricant into a mixer, placing the mixture under stirring at 175° C. for 0.5 h, and then extruding and granulating the mixture at 225° C. using a twin-screw extruder to obtain a mixture; S2. Blowing the mixture into the degradable antibacterial film material through a film blowing machine, wherein the film blowing machine is a three-screw film blowing machine, the screw processing temperature is set to 180° C., and the blowing die processing temperature is set to 200° C.
[0021] Example 3 A degradable antibacterial film material comprises the following components in parts by weight: 85 parts of polybutylene terephthalate-adipate, 9 parts of the modifying additive prepared in Example 1, 1.5 parts of diisononyl phthalate as a plasticizer, and 2 parts of zinc stearate as a lubricant.
[0022] The preparation method of the above-mentioned degradable antibacterial film material is the same as that in Example 2.
[0023] Example 4 A degradable antibacterial film material comprises the following components in parts by weight: 92 parts of polybutylene terephthalate-adipate, 14 parts of the modifying additive prepared in Example 1, 2.5 parts of dibutyl phthalate as a plasticizer, and 3 parts of polyethylene wax as a lubricant.
[0024] The preparation method of the above-mentioned degradable antibacterial film material is the same as that in Example 2.
[0025] Comparative Example 1 A method for preparing a modified additive comprises the following steps: (1) 7 mL of tetrabutyl titanate and 7 mL of anhydrous ethanol were stirred and mixed, 5 g of montmorillonite and 40 mL of deionized water were added, and the mixture was stirred for 0.5 h. Then, a mixed solution of 5 mL of acetic acid and 5 mL of deionized water was added, and the mixture was stirred evenly and allowed to stand for 24 h. The mixture was then dried in an oven and calcined at 600 °C for 5 h to prepare a composite filler. (2) 2.5 g of the composite filler was ultrasonically dispersed in 40 mL of toluene, and then a mixed solution of 1.2 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 20 mL of toluene was added, and the mixture was stirred at 85 °C for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried to prepare an epoxidized composite filler; (3) 2.5 g of the epoxidized composite filler was ultrasonically dispersed in 50 mL of anhydrous ethanol, and then a mixed solution of 0.73 g of 1,5-naphthalenediamine and 20 mL of anhydrous ethanol was added, and the mixture was stirred at 65 °C for 7 h. After the reaction was completed, the mixture was filtered, washed, and dried to prepare an amino composite filler; (4) 1 g of amino-modified composite filler was ultrasonically dispersed in 120 mL of anhydrous ethanol, 60 mL of cinnamaldehyde was added and stirred, and the mixture was stirred and reacted at 65 °C for 32 h under nitrogen conditions. After the reaction was completed, the modified composite filler was prepared by centrifugation, washing, and drying; (5) Cinnamon essential oil was added to the modified composite filler by vacuum adsorption method. The mass ratio of cinnamon essential oil to modified composite filler was 1:5. The mixture was evenly mixed and then placed under 0.1 MPa for vacuum adsorption for 2 h. After centrifugation to separate excess natural antibacterial agent, the modified additive was prepared.
[0026] Comparative Example 2 A method for preparing a modified additive comprises the following steps: (1) 7 mL of tetrabutyl titanate and 7 mL of anhydrous ethanol were stirred and mixed, 5 g of montmorillonite and 40 mL of deionized water were added, and the mixture was stirred for 0.5 h. Then, a mixed solution of 5 mL of acetic acid and 5 mL of deionized water was added, and the mixture was stirred evenly and allowed to stand for 24 h. The mixture was then dried in an oven and calcined at 600 °C for 5 h to prepare a composite filler. (2) 2.5 g of the composite filler was ultrasonically dispersed in 40 mL of toluene, and then a mixed solution of 1.2 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 20 mL of toluene was added, and the mixture was stirred at 85 °C for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried to prepare an epoxidized composite filler; (3) 2.5 g of the epoxidized composite filler was ultrasonically dispersed in 50 mL of anhydrous ethanol, and then a mixed solution of 0.73 g of 1,5-naphthalenediamine and 20 mL of anhydrous ethanol was added, and the mixture was stirred at 65 °C for 7 h. After the reaction was completed, the mixture was filtered, washed, and dried to prepare an amino composite filler; (4) 2.5 g of the amino composite filler was ultrasonically dispersed in 100 mL of anhydrous ethanol to obtain a dispersion, and then 2.5 g of a 50 wt% phytic acid aqueous solution was dissolved in 50 mL of anhydrous ethanol and added to the dispersion. The mixture was stirred at 70° C. for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a flame-retardant composite filler. (5) 1 g of flame-retardant composite filler was ultrasonically dispersed in 120 mL of anhydrous ethanol, and then a mixed solution of 4.3 g of zinc acetate dihydrate and 50 mL of deionized water was added, and the mixture was stirred at 45 °C for 6 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to prepare a modified flame-retardant composite filler; (6) Cinnamon essential oil was added to the modified flame retardant composite filler by vacuum adsorption method. The mass ratio of cinnamon essential oil to modified flame retardant composite filler was 1:5. The mixture was evenly mixed and then placed under 0.1 MPa for vacuum adsorption for 2 h. After centrifugation to separate excess natural antibacterial agent, the modified additive was prepared.
[0027] Comparative Example 3 A method for preparing a modified additive comprises the following steps: (1) 7 mL of tetrabutyl titanate and 7 mL of anhydrous ethanol were stirred and mixed, 5 g of montmorillonite and 40 mL of deionized water were added, and the mixture was stirred for 0.5 h. Then, a mixed solution of 5 mL of acetic acid and 5 mL of deionized water was added, and the mixture was stirred evenly and allowed to stand for 24 h. The mixture was then dried in an oven and calcined at 600 °C for 5 h to prepare a composite filler. (2) Cinnamon essential oil was added to the composite filler by vacuum adsorption method. The mass ratio of cinnamon essential oil to composite filler was 1:5. The mixture was evenly mixed and then placed under 0.1 MPa for vacuum adsorption for 2 h. After centrifugation to separate the excess natural antibacterial agent, the modified additive was prepared.
[0028] Comparative Example 4 A degradable antibacterial film material comprises the following components in parts by weight: 92 parts of polybutylene terephthalate-adipate, 14 parts of the modified additive prepared in Comparative Example 1, 2.5 parts of dibutyl phthalate as a plasticizer, and 3 parts of polyethylene wax as a lubricant.
[0029] The preparation method of the above-mentioned degradable antibacterial film material is the same as that in Example 2.
[0030] Comparative Example 5 A degradable antibacterial film material comprises the following components in parts by weight: 92 parts of polybutylene terephthalate-adipate, 14 parts of the modified additive prepared in Comparative Example 2, 2.5 parts of dibutyl phthalate as a plasticizer, and 3 parts of polyethylene wax as a lubricant.
[0031] The preparation method of the above-mentioned degradable antibacterial film material is the same as that in Example 2.
[0032] Comparative Example 6 A degradable antibacterial film material comprises the following components in parts by weight: 92 parts of polybutylene terephthalate-adipate, 14 parts of the modified additive prepared in Comparative Example 3, 2.5 parts of dibutyl phthalate as a plasticizer, and 3 parts of polyethylene wax as a lubricant.
[0033] The preparation method of the above-mentioned degradable antibacterial film material is the same as that in Example 2.
[0034] Performance Testing The film materials prepared in Examples 2-4 and Comparative Examples 4-6 were subjected to performance testing: (1) Mechanical properties testing: The tensile strength and elongation at break of the film with a size of 20 mm × 150 mm were tested using an intelligent electronic tensile testing machine. The tensile rate was set to 50 mm / min. The data results are shown in Table 1.
[0035] (2) Water vapor permeability test: The film was equilibrated in an environment of 23°C and 50% relative humidity for 24 hours before the test. The data results are shown in Table 1.
[0036] (3) Oxygen permeability test: The film was equilibrated in an environment of 23°C and 50% relative humidity for 24 h before the test. The test gas was high-purity oxygen (purity of 99.999%, expressed as volume fraction). The data results are shown in Table 1.
[0037] (4) Flame retardant performance test: The flame retardant performance of the film material was evaluated by the limiting oxygen index, and the data results are shown in Table 1.
[0038] (5) Antibacterial performance test: The plate count method was used to test the antibacterial effect on Escherichia coli and Staphylococcus aureus. The activated bacterial solution was added to the test tube and diluted to a total bacterial colony count of 10. 5 ~10 6 CFU / mL, add the film to the bacterial solution, and the bacterial solution without film is used as the control group. Put the test tube in a constant temperature incubator and shake it for 24 hours at 37℃. Then take a certain amount of diluted bacterial solution and apply it on the agar medium. Put it in a constant temperature incubator and observe the number of colonies in each culture dish after culturing at 37℃ for 24 hours. The number of colonies is calculated by the number of colonies (I). The calculation formula is: I= (A0-A1) / A0, where A0 is the number of colonies without film, and A1 is the number of colonies with film. The data results are shown in Table 1.
[0039] Table 1 Test results of sample performance
[0040] It can be seen from the data in Table 1 that the film materials prepared in Examples 2-4 of the present invention have high tensile strength, are not easy to break, have low air permeability and oxygen permeability, good barrier properties, and have excellent antibacterial effect and flame retardant properties. Among them, the modified additive component added in Comparative Example 4 is not grafted with phytic acid and zinc ions are not introduced, and its measured flame retardant properties are lower than those of Examples 2-4. The modified additive component added in Comparative Example 5 is not grafted with cinnamaldehyde, and its measured antibacterial properties are lower than those of Examples 2-4, indicating that the grafting of cinnamaldehyde can further improve the antibacterial properties.
[0041] In Comparative Example 6, the modified additive component replaces the modified flame-retardant composite filler with an equal amount of composite filler. The measured antibacterial and flame-retardant properties are significantly lower than those of Examples 2-4. The reason is that the composite filler is not grafted with antibacterial and flame-retardant components. The measured tensile strength and elongation at break are lower than those of Examples 2-4. The possible reason is that the agglomeration of the composite filler causes its mechanical properties to decrease, and the agglomeration phenomenon causes a few gaps or defects at the interface between the composite filler and the resin, providing more diffusion channels for water vapor, thereby increasing the water vapor permeability compared with Example 2-4. In addition, the measured oxygen permeability is higher than that of Example 2-4. The reason is that the modification of the composite filler can increase the interlayer spacing of montmorillonite, and oxygen is forced to pass through a longer path to penetrate.
[0042] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0043] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A degradable antibacterial film material, characterized in that: The invention comprises the following components in parts by weight: 75-100 parts of a degradable base resin, 5-15 parts of a modification additive, 1-3 parts of a plasticizer, and 1-3 parts of a lubricant; The modified additive is made by loading a natural antibacterial agent on a modified flame-retardant composite filler; The modified flame retardant composite filler is prepared by using cinnamaldehyde to react with the flame retardant composite filler to form a complex with zinc acetate dihydrate; The flame-retardant composite filler is prepared by a ring-opening reaction between an epoxidized composite filler and 1,5-naphthalenediamine, followed by a nucleophilic substitution reaction with phytic acid; the epoxidized composite filler is prepared by a sol-gel method for preparing a composite filler of montmorillonite loaded with nano-titanium dioxide, and then modified with 3-(2,3-epoxypropoxy)propyltrimethoxysilane.
2. The degradable antibacterial film material according to claim 1, characterized in that: The degradable matrix resin is one or more combinations of polybutylene terephthalate-adipate, polylactic acid, polyε-caprolactone, polyglycolic acid, and polyhydroxyalkanoate.
3. The degradable antibacterial film material according to claim 1, characterized in that: The plasticizer is one or more combinations of tributyl citrate, diisononyl phthalate, dibutyl phthalate, and acetyl tributyl citrate; the lubricant is one or more combinations of stearic acid, zinc stearate, polyethylene wax, and paraffin.
4. The degradable antibacterial film material according to claim 1, characterized in that: The preparation method of the modified additive comprises the following steps: (1) Tetrabutyl titanate and anhydrous ethanol are stirred and mixed, montmorillonite and deionized water are added, and the stirring is continued for 0.5 to 1 hour, and then a mixed solution of acetic acid and deionized water is added, and the mixture is stirred evenly and allowed to stand for 20 to 24 hours, and then dried in an oven, and then calcined at 550 to 650° C. for 4 to 7 hours to prepare a composite filler; (2) ultrasonically dispersing the composite filler in toluene, then adding a mixed solution of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and toluene, stirring and reacting at 80-95°C for 5-6 hours, and after the reaction is completed, filtering, washing and drying to prepare an epoxidized composite filler; (3) ultrasonically dispersing the epoxidized composite filler in anhydrous ethanol, then adding a mixed solution of 1,5-naphthalenediamine and anhydrous ethanol, stirring and reacting at 55-70° C. for 5-8 hours, and filtering, washing and drying after the reaction to obtain an amino composite filler; (4) ultrasonically dispersing the amino composite filler in anhydrous ethanol to obtain a dispersion, then dissolving the phytic acid aqueous solution in anhydrous ethanol and adding it to the dispersion, stirring and reacting at 60-75° C. for 4-6 hours, filtering, washing and drying after the reaction is completed to prepare a flame-retardant composite filler; (5) Ultrasonic dispersion of flame-retardant composite filler in anhydrous ethanol, adding cinnamaldehyde and stirring the mixture, stirring the mixture at 60-70°C for 28-36 hours under nitrogen conditions, then adding a mixed solution of zinc acetate dihydrate and deionized water, stirring the mixture at 40-50°C for 4-6 hours, and after the reaction is completed, centrifuging, washing, and drying to obtain a modified flame-retardant composite filler; (6) The natural antibacterial agent is added to the modified flame retardant composite filler by vacuum adsorption method, mixed evenly, and then vacuum adsorbed for 1 to 3 hours. After centrifugation to separate the excess natural antibacterial agent, the modified additive is prepared.
5. The degradable antibacterial film material according to claim 4, characterized in that: In the step (2), the mass ratio of the composite filler to 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 1:0.4-0.
7.
6. The degradable antibacterial film material according to claim 4, characterized in that: In the step (3), the mass ratio of the epoxidized composite filler to 1,5-naphthalene diamine is 1:0.25-0.
45.
7. The degradable antibacterial film material according to claim 4, characterized in that: The mass concentration of the phytic acid aqueous solution in step (4) is 40-60wt%; the mass ratio of the amino composite filler to the phytic acid aqueous solution is 1:1-2.
5.
8. The degradable antibacterial film material according to claim 4, characterized in that: In the step (5), the addition ratio of the flame retardant composite filler, cinnamaldehyde and zinc acetate dihydrate is 1 g: 40-70 mL: 3.5-5.5 g.
9. The degradable antibacterial film material according to claim 4, characterized in that: In step (6), the natural antibacterial agent is one or more combinations of clove essential oil, cinnamon essential oil, lemongrass essential oil, thyme essential oil, garlic essential oil, oregano essential oil, lemon essential oil, tea tree essential oil, rosemary extract, olive leaf extract, and grape seed extract.
10. A method for preparing the degradable antibacterial film material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, taking parts by weight of a biodegradable base resin, a modifying additive, a plasticizer and a lubricant into a mixer, placing the mixture at 150-200° C. and stirring for 0.5-1 h, and then extruding and granulating the mixture at 200-230° C. using a twin-screw extruder to obtain a mixture; S2. Blowing the mixture into the degradable antibacterial film material through a film blowing machine, wherein the film blowing machine is a three-screw film blowing machine, the screw processing temperature is set to 160-180° C., and the blowing die processing temperature is set to 190-210° C.
Citation Information
Patent Citations
Biodegradable flame-retardant plastic film and preparation method thereof
CN104448495A
Edible food packaging film and preparation method thereof
CN109233001A
Degradable plastic packaging material and preparation process thereof
CN115073897A
Bio-based phosphorus-nitrogen flame-retardant PLA (polylactic acid) composite material as well as preparation method and application thereof
CN115710418A
Disposable degradable lunch box and preparation method thereof
CN116285104A
Cited By
Biodegradable plastic bag and preparation method thereof
CN120464160A
Biodegradable polylactic acid plastic bag and preparation method thereof
CN120758004A
High-performance polypropylene material for food packaging and preparation method thereof
CN121021983A